EFEKTIVITAS IMPLEMENTASI KEBIJAKAN ANTI PENDANAAN TERORISME DI INDONESIA DALAM MENGURANGI KASUS TERORISME TRANSNASIONAL - Zulfikar, Faisal Mufti; Ayu, Andina Mustika; Saputro, Pradono Budi (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
The development of transnational terrorism has made countries in the world aware of the threat of terror groups that can threaten the stability of the country, one of which is Indonesia. Terror groups before carrying out attack activities, of course, begin with funding efforts first. Funding is an important basis in all forms of terrorism activities. With the development of the times, the way terror groups fund their actions is also increasingly varied, such as through banks, carrying money directly, using charity activities, and so on. Indonesia responds to these challenges by implementing policies, ranging from drafting anti-terrorism funding laws, conducting international cooperation, and establishing institutions as an effort to overcome terror funding traffic. In analysing the phenomenon in this study, the researcher used Grindle's policy implementation theory supported by the concepts of terrorism and terrorism financing. This research uses a qualitative approach and analytical descriptive research type. Therefore, the purpose of this research is to see the effectiveness of policy implementation conducted by Indonesia in an effort to suppress transnational terrorism cases. As a measure of the success or failure of Indonesia's implementation in tackling terrorism financing, the researcher sees it through the number of terror activities since the policy has been made by Indonesia. Although it is said to be successful, there still needs to be adjustments to the development of terror groups in Indonesia. Keywords: Policy Implementation, Anti-Terrorism Financing Policy, Terrorism Financing